2013
DOI: 10.1038/modpathol.2012.148
|View full text |Cite
|
Sign up to set email alerts
|

Pyogenic granuloma, an impaired wound healing process, linked to vascular growth driven by FLT4 and the nitric oxide pathway

Abstract: Pyogenic granuloma, also called lobular capillary hemangioma, is a condition usually occurring in skin or mucosa and often related to prior local trauma or pregnancy. However, the etiopathogenesis of pyogenic granuloma is poorly understood and whether pyogenic granuloma being a reactive process or a tumor is unknown. In an attempt to clarify this issue, we performed genome-wide transcriptional profiling of lasercaptured vessels from pyogenic granuloma and from a richly vascularized tissue, placenta, as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 52 publications
0
35
0
2
Order By: Relevance
“…Reactive vascular proliferative lesions were grouped with benign tumors. The distinction between the reactive or tumor nature of a lesion is not always straightforward and is debated for several lesions (pyogenic granuloma/ lobular capillary hemangioma, 16 spindle cell hemangioma, 17 epithelioid hemangioma 18 ). Some rare vascular tumors are not included in the table and are listed as "others,"…”
Section: Vascular Tumorsmentioning
confidence: 99%
“…Reactive vascular proliferative lesions were grouped with benign tumors. The distinction between the reactive or tumor nature of a lesion is not always straightforward and is debated for several lesions (pyogenic granuloma/ lobular capillary hemangioma, 16 spindle cell hemangioma, 17 epithelioid hemangioma 18 ). Some rare vascular tumors are not included in the table and are listed as "others,"…”
Section: Vascular Tumorsmentioning
confidence: 99%
“…Interestingly, drug-associated pyogenic granulomas tend to have a periungual and subungual distribution [10]. Recent insights from gene expression profiling identify FLT4 (a specific VEGF receptor), the nitric oxide pathway and vascular injury and repair pathways as specifically upregulated in pyogenic granulomas compared to other vascular proliferative lesions [12]. How the molecular underpinnings connect to the diverse set of reported triggers remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…A recent genetic study on vessels derived from cutaneous PG lesion identified a gene signature including genes of the nitric oxide pathway and those related to hypoxia-induced angiogenesis and vascular injury, like the tyrosine-kinase receptor FTL4 [18]. Thus, PG may be regarded as a reactive lesion resulting from tissue injury, followed by an impaired wound healing response, during which vascular growth is driven by FLT4 and the nitric oxide pathway.…”
Section: Discussionmentioning
confidence: 99%